Land Use Planning and Green Environment Services: The Contribution of Trail Paths to Sustainable Development - Kyriakopoulos, Grigorios L. (Land (Basel), 2023)
Recently land-use planning and green environment services have been considered as inseparable parts of the design of trail paths for a sustainable development. At present there is need of a holistic overview of land uses and land cover, to be linked with the natural environment and regional development. The key determinants of such an approach embody changes in the wake of drivers and anthropocentric changes as well as changes in global greenhouse gases, causing climate change and affecting global biodiversity. In this study the key determinants and the main research objects of previously developed studies were systematically approached by a search of the literature through the Scopus database using these four fields of keywords: (a) “land use” AND environment AND development, (b) “trail path” in the “article titles” AND the subcategory of “land”, (c) “land use” AND “sustainable development”, and, (d) “sustainable” AND “trail”. The derived documents were collected and organized into the following four main domains, being paired together by: (a) year and country/territory, and, (b) keyword and subject area. The classification of the documents was followed by the calculation of relevant “intensity ratios” as key determinants that disclose the well-defined and the emerging fields of further perspectives regarding land use planning and the particular emerging dynamics of the development of trail paths.